Analisis Yuridis terhadap Penguatan Prinsip Praduga Tak Bersalah dalam Rangka Pencegahan Tindakan Salah Tangkap - Mufty, Abdulmalik; DM, Nur Sri Maryam (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2025)
This study analyzes the strengthening of the presumption of innocence principle in Indonesia's criminal justice system to prevent wrongful arrests by the police. Using normative legal research methods with statutory and conceptual approaches, the study examines primary legal sources (Criminal Procedure Code, Police Law), secondary (legal literature), and tertiary materials. Findings reveal three main issues: (1) regulatory weaknesses including unclear standards for preliminary evidence and excessive discretionary authority, (2) confession-oriented investigative culture, and (3) lack of effective victim recovery mechanisms. The research proposes comprehensive solutions including: regulatory reform through improved evidence standards and judicial review mechanisms, transformation of investigative culture through human rights-based training, strengthening of independent oversight, and implementation of technology for procedural transparency. These solutions require an integrated approach incorporating adapted global best practices such as the warrant system (UK) and Miranda rights (US) modified for local context. Expected outcomes include a fairer criminal justice system with reduced wrongful arrests, enhanced professional standards for law enforcement, and comprehensive protection of suspect rights. The study makes significant contributions to the development of due process theory and judicial system reform in Indonesia. The proposed multidimensional approach balances effective law enforcement with human rights protection, offering practical policy recommendations for creating a justice system that upholds the rule of law while maintaining public trust. Implementation requires political commitment, institutional capacity building, and phased technological integration over a five-year roadmap.